Taking College Esports Seriously - Kauweloa, Nyle Sky; Winter, Jenifer Sunrise (Loading, 2019)
This study examined how collegiate esports players conceptualized their own competitive gameplay as situated between work and play. Using interviews guided by Stebbins’ (2007) serious leisure perspective, 16 collegiate esports players described how belonging to a collegiate esports team has shaped their identity, and how they experienced gaming within the structured environment of a collegiate esports team and club. Stebbins’ description of skill and knowledge development was supported, and the findings are in accord with Stebbins’ conceptualization of “personal rewards,” such as self-expression, self-image, and self-actualization.